Effect of pulping conditions and beating on Semantan bamboo pulp and paper properties / Nurul Husna Mohd Hassan - Mohd Hassan, Nurul Husna (Institute of Research, Development and Commercialization (IRDC), 2013)
The fiber morphology such as fiber length, fiber diameter and lumen diameter for Semantan bamboo were determined and the means were 3.02 mm, 19.83 μm and 9.58 μm respectively. Semantan bamboo chemical composition namely ethanol-toluene solubility, lignin, holocellulose and alpha-cellulose were also determined and the means ranged from 1.68 – 4.12%, 22.31 – 23.56%, 73.48 – 74.66% and 49.02 – 49.93% respectively. Semantan bamboo soda-AQ pulping were done according to the bamboo portion and pulping screened yield ranged from 33.69 – 41.82%. Results from unbeaten paper making showed relatively low paper properties where the tensile index, tearing index, bursting index and folding endurance ranged from 16.52 – 32.54 Nm/g, 9.59 – 13.45 mN.m2/g, 0.8 – 1.5 kPa.m2/g and 3 – 9 double folds respectively. The top portion of the bamboo was chosen based on the highest paper strength produced from unbeaten paper for the paper making that involved beating process from 1000 to 24000 beating revolutions. The purpose for this stage of the research was to determine the optimum beating process for the paper making in the next part…